2009
DOI: 10.1155/2009/532640
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of Autism Is Associated with Toxic Metal Body Burden and Red Blood Cell Glutathione Levels

Abstract: This study investigated the relationship of children's autism symptoms with their toxic metal body burden and red blood cell (RBC) glutathione levels. In children ages 3–8 years, the severity of autism was assessed using four tools: ADOS, PDD-BI, ATEC, and SAS. Toxic metal body burden was assessed by measuring urinary excretion of toxic metals, both before and after oral dimercaptosuccinic acid (DMSA). Multiple positive correlations were found between the severity of autism and the urinary excretion of toxic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 14 publications
6
83
0
Order By: Relevance
“…There has been a dramatic increase in exposure to mercury in the last twenty years (Schuster et al 2002), an increase in detected blood mercury levels in the US population (Laks 2009), and a dramatic increase in the rates of autism (Kalia 2008;Hertz-Picciotto and Delwiche 2009;Hertz-Picciotto 2009;Rutter 2005). Many studies have shown an association between mercury and autism (Lopez-Hertado and Prieto 2008;DeSoto and Hitlan 2007;Adams et al 2007), and some studies have also indicated a role of other toxic metals (Adams et al 2009); however, this present study takes the investigation one step further and shows an association between mercury toxicity and the specific hallmark features of autism and PDD-NOS.…”
Section: Resultsmentioning
confidence: 99%
“…There has been a dramatic increase in exposure to mercury in the last twenty years (Schuster et al 2002), an increase in detected blood mercury levels in the US population (Laks 2009), and a dramatic increase in the rates of autism (Kalia 2008;Hertz-Picciotto and Delwiche 2009;Hertz-Picciotto 2009;Rutter 2005). Many studies have shown an association between mercury and autism (Lopez-Hertado and Prieto 2008;DeSoto and Hitlan 2007;Adams et al 2007), and some studies have also indicated a role of other toxic metals (Adams et al 2009); however, this present study takes the investigation one step further and shows an association between mercury toxicity and the specific hallmark features of autism and PDD-NOS.…”
Section: Resultsmentioning
confidence: 99%
“…Many investigations indicate that autistic children have a decreased ability to excrete toxic metals and the reduced excretion combined with the relatively long half-life of these elements lead to their accumulation in tissues (Adams et al 2012). Moreover, the level of toxic metal body burden seems to be associated with the severity of autism symptoms, as shown by Adams et al (2009) who measured the body burden of toxic metals by giving dimercaptosuccinic acid, an oral chelator, and measuring the urinary excretions of metallic elements before and after the drug treatment. Collectively, increasing evidence suggests a significant relationship between environmental exposures in parents and children to Pb and MeHg and development of ASDs, though further investigation in this area is warranted due to the different background conditions of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, several lines of research have shown that autistic children display a higher body burden of toxic metals compared to neurotypical controls (Adams et al 2009;Elsheshtawy et al 2011;Lakshmi Priya and Geetha 2011). In addition, the impact of heavy metals seems to be more evident in subjects with moderate or severe ASD in comparison to subjects with mild ASD (Geier et al 2009a(Geier et al , b, 2012.…”
mentioning
confidence: 99%
“…Thus, a lower level of mitochondrial reduced-glutathione (GSH, a natural antioxidant defense mechanism) existed in individuals with ASD, as compared to unaffected ones. Moreover, ASD severity has been inversely associated with GSH levels and other biological markers of cellular OS [24][25][26]. Furthermore, postmortem brain samples from ASD patients demonstrated low levels of GSH and altered activity of antioxidant-enzymes, along with clues of massive oxidative damage to proteins, enzymes and DNA, with mounting levels of lipid peroxides [26][27][28].…”
Section: Epigenetic Modifications and Interplay With Environmental Famentioning
confidence: 99%